2004
DOI: 10.1007/s00330-004-2553-4
|View full text |Cite
|
Sign up to set email alerts
|

MR relaxometry and 1H MR spectroscopy for the determination of iron and metabolite concentrations in PKAN patients

Abstract: The influence of iron deposits on T2 values and the content of metabolites in the brain of three patients with DNA proved pantothenate kinase-associated neurodegeneration (PKAN, formerly Hallervorden-Spatz syndrome) was studied. An eye-of-the-tiger sign, a typical MR finding for PKAN, was observed in two patients with the same mutation. A hypointensive lesion in a whole globus pallidus was observed in the third patient with the additional mutation. T2 values in the globus pallidus of the patients were about 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
5
22
2
Order By: Relevance
“…Due to the limited resolution of the SI data and the omission of the correction for CSF content in each voxel, the concentration values are subject to partial volume effects. The metabolite image shows an increased concentration of Cr in the basal ganglia, which is in accordance with the published data[21,22]. On the other hand, the image shows very low Cr concentrations in the middle frontal region.…”
supporting
confidence: 90%
“…Due to the limited resolution of the SI data and the omission of the correction for CSF content in each voxel, the concentration values are subject to partial volume effects. The metabolite image shows an increased concentration of Cr in the basal ganglia, which is in accordance with the published data[21,22]. On the other hand, the image shows very low Cr concentrations in the middle frontal region.…”
supporting
confidence: 90%
“…jpet.aspetjournals.org levels are high in vulnerable brain regions and are increased further in these diseases (Zecca et al, 2004). The iron concentration that we used is similar to that used in other in vitro studies of iron neurotoxicity (Liu et al, 2003) and within the range of concentrations found in mouse and human brain (Griffiths et al, 1999;Moos et al, 2000;Zecca et al, 2001;Hajek et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…5). As these results had been theoretically forecasted based on published experimental studies [23,24], no correction for multiple comparisons was employed in the statistical analysis of these data. The correlation for the right pallidum and caudate were slightly less than statistically significant.…”
Section: Correlation Between Relaxometry Clinical and Genetic Paramementioning
confidence: 99%